Role Of Ergonomics In Occupational Health Problems Of Information Technology Professional Of Ahmedabad City (Indian Journal of Public Health Research & Development, 2024)
Abstract:Background: Computer ergonomics is crucial for optimizing the interaction between individuals and their computer workstations to enhance overall well-being and productivity. By designing workspaces that consider the capabilities and limitations of the human body, computer ergonomics aims to prevent musculoskeletal disorders, reduce eye strain, and mitigate stress-related issues associated with prolonged computer use.Material & Method: It was cross actional study carried out in computer users of Ahmedabad city. Cross sectional study was carried out over a period of one year time among 800 participants to Study the knowledge and practice pertaining to computer ergonomics and obstacle for not following it.Results: Only 359 (44.87%) participants were aware of the computer ergonomics. Main source of information was internet (47.91%). 35.65% of the participants were aware of computer ergonomics before any health problem occurred to them, while 64.34% participants became aware to computer ergonomics after occurrence of musculoskeletal or visual problem.Conclusions: Appropriate furniture, appropriate monitor distance, change in brightness according to need and appropriate body posture had vital role in prevention of computer related health problem. In conclusion, the data highlights the need for widespread initiatives to enhance awareness of computer ergonomics, leveraging internet resources and incorporating structured training programs.